2021
DOI: 10.1002/cjce.24285
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3 and CuO nanoparticles as promising additives to improve the properties of KCl‐polymer mud: An experimental investigation

Abstract: Drilling fluid technology is one of the most targeted and developed technologies worldwide due to the increasing demand for deeper drilling and more complicated wells. Several studies have shown numerous improvements in the mud characteristics when using nanoparticles (NPs) as additives. This study aims at examining the influence of using aluminium oxide (Al2O3) and copper oxide (CuO) NPs on the characteristics of KCl‐polymer mud, which is mainly used while drilling shaly formations. Two sizes of Al2O3‐NPs (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…The quality of filter cake with respect to fluid loss and mechanical strength depends on the additives in the drilling fluids such as fluid loss control polymers as well as the packing of solids deposited in the mud cake. Several investigators have reported the impact of nanoparticles that reduce the filtrate loss such as (Fe 2 O 3 , [ 15 ], SnO 2 [ 17 ] MWCNT, Al 2 O 3 , CuO, TiO 2 [ 16 , 19 ], MWCNT, Graphene, [ 18 ], Fe 2 O 3 , [ 20 ]) and silica reduce the permeability of the shale by plugging the pore spaces [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of filter cake with respect to fluid loss and mechanical strength depends on the additives in the drilling fluids such as fluid loss control polymers as well as the packing of solids deposited in the mud cake. Several investigators have reported the impact of nanoparticles that reduce the filtrate loss such as (Fe 2 O 3 , [ 15 ], SnO 2 [ 17 ] MWCNT, Al 2 O 3 , CuO, TiO 2 [ 16 , 19 ], MWCNT, Graphene, [ 18 ], Fe 2 O 3 , [ 20 ]) and silica reduce the permeability of the shale by plugging the pore spaces [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, MoS 2 impact on the thermal stable drilling fluids enhances the lubricity, electrical and heat conductivity properties without impacting the thermal stability rheological behavior of the base fluids. In terms of filtrate losses, several investigators reported that different nanoparticle reduced the filtrate loss [ 15 , 16 , 17 , 18 , 19 , 20 ]. On the other hand, MoS 2 used in this paper did not show any reduction impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Particularly, dielectric AlO x NPs and TiO 2 NRs/NPs as a semiconductor demonstrating high mechanical-electrical-thermal stability, high-performance materials can be exclusively rearranged as a 1 st , 2 nd , and 3 rd core layers respectively on consecutive substrate surface. [14][15][16][17][18][19][20][21][22][23][24] In addition, implementation of NRs into manufactured nanostructures is appropriate due to improvement of electrical properties in terms of electron transport rate. [25][26][27][28] Furthermore, the addition of NRs into NP system diminishes the resistance of charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…The Canadian Journal of Chemical Engineering is acknowledged for dedicating this special issue to the living memory of Dr. Nasr‐El‐Din. This acknowledgment is also extended to the authors who contributed to this special issue [ 1–28 ] as well as the guest editors:…”
mentioning
confidence: 99%